Quality of life in Malaysian children with epilepsy - Fong, Choong Yi; Chang, Wei Mun; Kong, Ann Nie; Rithauddin, Ahmad Mohamed; Khoo, Teik Beng; Ong, Lai Choo (Elsevier, 2018)
Background: Children with epilepsy (CWE) are at risk of impaired quality of life (QOL), and achieving a good QOL is an important treatment goal among CWE. To date, there are no published multiethnic QOL studies in Asia. Our study aimed to: i) investigate the QOL of multiethnic CWE in Malaysia as reported by both the child and parent; ii) determine the level of agreement between child-self report and parent-proxy report QOL; and iii) explore potential correlates of sociodemographic, epilepsy characteristics, and family functioning with QOL in CWE. Methods: Cross-sectional study of all CWE aged 8–18 years old with at least 6 months' duration of epilepsy, minimum reading level of primary school education Year 1, and attending mainstream education. Quality of life was measured using the parent-proxy and child self-report of Quality of Life Measurement for Children with Epilepsy (CHEQOL-25) questionnaire. Total and subscale CHEQOL-25 scores were obtained. The levels of parent–child agreement were determined using intraclass correlation coefficients (ICC). Family functioning was assessed using the General functioning subscale (GF-12). Results: A total of 115 CWE and their parents participated in the study. In general, Malaysian parents rated children's total CHEQOL-25 scores poorer than the children themselves [mean total parent score: 68.56 (SD: 10.86); mean total child score: 71.82 (SD: 9.55)]. Agreement between child and parent on the CHEQOL-25 was poor to moderate (ICC ranged from 0.31–0.54), with greatest discordance in the epilepsy secrecy domain (ICC = 0.31, p = 0.026). Parent and child were more likely to agree on more external domains: intrapersonal/social (ICC = 0.54, p < 0.001) and interpersonal/emotional (ICC = 0.50, p < 0.001). Malay ethnicity, focal seizure and high seizure frequency (≥ 1 seizure per month) were associated with lower CHEQOL-25 scores. There was a significant but weak correlation between GF-12 and parent–proxy CHEQOL-25 Total Scores (r = − 0.186, p = 0.046). Conclusion: Our results emphasize the importance to have the child's perspective of their QOL as the level of agreement between the parent and child reported scores were poor to moderate. Malaysian CWE of Malay ethnicity, those with focal seizures or high seizure frequency are at risk of poorer QOL.